CLINICAL CHARACTERISTICS AND MANAGEMENT OF OCULAR TOXOPLASMOSIS - Ovi Sofia; Rizqi Wahyu Hariyono (Indonesian Vitreoretinal Society, 2019)
Introduction: Ocular toxoplasmosis is a major cause of infectious posterior uveitis worldwide. There was no exact number of ocular toxoplasmosis prevalence in Indonesia, but Indonesia was considered to have high seroprevalence in Southeast Asian. This study is conducted to determine clinical characteristics and management of ocular toxoplasmosis at outpatient clinic of Dr. Saiful Anwar General Hospital, a tertiary referral hospital in Malang, East Java. Methods : This was retrospective study. We reviewed the medical records of patients with ocular toxoplasmosis and collected the data associated with age, sex, laterality, visual outcome, type of lesions, serum serological titers, therapeutic regimens, and complications. Result : There were 48 eyes from 38 patients included in this study, mostly were female (66%) with mean age was 33,5 years. Unilateral infection (71%) was more frequent than bilateral cases (39%). Active lesions were found more than cicatrical lesions (56,25%). Most patients with active diseases had unilateral lesion (87,5%). The most common presenting complain was blurred vision (73%). Most of lesions (22 eyes; 81,4%) were located on macular region. All of patients have positive IgG antitoxoplasma serum. There were 22 patients received oral Trimethoprim-Sulfamethoxazole and steroid. Visual acuity improved in 6 patients at the end of follow-up period. Complications of retinal detachment and choroidal neovascularization were found in 3 patients. Conclusion : Active ocular toxoplasmosis is more likely to be unilateral infection with main presenting complain is blurred vision. Most of our patients show good responses to oral trimethoprim-sulfamethoxazole and steroid.